Antifungal Effect of Some Medicinal Plant Extracts On Candida Albicans Adherence on Acrylic Resin Denture Base Material. An In Vitro Study - Tarik Y.Kassab -Bashi; Ghada Y.Abdul -Rahman; Nagham Hazim kassab (University of Mosul, College of Dentistry, 2014)
Evaluate the antifungal effect of some medicinal plant extracts (peppermint, rue, pomegranate and garlic) and their anti-adherent effect on C. albicans cells that attached on the fitting surface of acrylic resin denture base. Materials and Methods: This study evaluated the antifungal effect of plant extracts, using broth micro dilution method at two concentrations for each one. The visualization, in-spection and enumeration of adherent C. albicans cells and the detection of the anti-adherent effect of these plant extracts was achieved by using fluorescent microscope. For each plant extract, two concen-trations in addition to the time of immersion at three different intervals (1 h, 24 hrs and 48 hrs) were evaluated for the anti-adherent effect. Result: Antifungal effect of plant extracts on candida albicans cells, was measured by spectrophotometer which showed that both rue and pomegranate extracts had the best antifungal effect at first concentration, while in the second concentration, pomegranate and garlic extracts had the best antifungal effect . The mean number of remaining C. albicans cells which adhered on acrylic resin samples after treatment by immersion in the first concentration of plant ex-tracts for one hour was (3.1), (3.7), (3.7) and (4.7)] cells /mm2 respectively; while after treatment with second concentration of plant extracts for one hour was [ (4), (4.4), (4.4) and (4)] cells / mm2 respec-tively for the above mentioned plant Conclusion: All examined medicinal plant extracts were signifi-cantly effective in dislodging C. albicans cells from acrylic resin samples at their different concentra-tions and statistically there was no significant difference among the different times of immersion.